2022
DOI: 10.32394/rpzh.2022.0202
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selected lifestyle factors on the nutrition state of elderly people with metabolic syndrome

Abstract: Background. The formation and development of the metabolic syndrome (MetS) is largely caused by lifestyle factors. Many studies have shown that excessive consumption of simple carbohydrates, alcohol, salt, physical inactivity and smoking increase the risk of MetS. Objective. The aim of the study was to assess the nutritional status and its relationship with selected lifestyle factors in elderly people with MetS. Material and methods. 81 people aged 51-75 participated in the study. According to the guidelines, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…49,50 The increase in body fat observed in both exercise groups suggests that it was not due to the effect of the types of exercises applied here but a change that can be attributed to the aging process itself and the chosen lifestyle. 51,52 It is possible that the exercise just induced a greater than-usual food avidity (not evaluated here), which could have contributed to the increase in body fat in both groups. 53 The increase in the overweight group was 30%.…”
Section: Discussionmentioning
confidence: 99%
“…49,50 The increase in body fat observed in both exercise groups suggests that it was not due to the effect of the types of exercises applied here but a change that can be attributed to the aging process itself and the chosen lifestyle. 51,52 It is possible that the exercise just induced a greater than-usual food avidity (not evaluated here), which could have contributed to the increase in body fat in both groups. 53 The increase in the overweight group was 30%.…”
Section: Discussionmentioning
confidence: 99%
“…According to the authors, in both groups, the most common errors involved eating irregularly, i.e., having an improper number of meals during the day and snacking between them ( 36 ). In turn, Pachocka et al, in their study of the impact of lifestyle on the level of nutrition in elderly people with metabolic syndrome, showed that 36% of people sweetened their beverages and 65.6% added salt to their food ( 37 ). As research shows, the quality of diet, including the number and regularity of meals, snacking, or the use of salt and sugar, is strongly associated with an increased risk of morbidity and even mortality due to CVD.…”
Section: Discussionmentioning
confidence: 99%